Advances in Primary Progressive Aphasia - Matias-Guiu, Jordi A.; Laforce, Robert Jr; Utianski, Rene L. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Primary progressive aphasia is a clinical syndrome that includes a group of neurodegenerative disorders characterized by progressive language impairment. Our knowledge about this disorder has evolved significantly in recent years. Notably, correlations between clinical findings and pathology have improved, and main clinical, neuroimaging, and genetic features have been described. Furthermore, primary progressive aphasia is a good model for the study of brain-behavior relationships, and has contributed to the knowledge of the neural basis of language functioning. However, there are many open questions remaining. For instance, classification into three variants (non-fluent, semantic, and logopenic) is under debate; further data about epidemiology and natural history of the diseases are needed; and, as in other neurodegenerative disorders, successful therapies are lacking. The Guest Editors expect that this book can be very useful for scholars.